Internal jugular vein ultrasound in patients with chronic congestive heart failure. (14th October 2021) - Thacker, P; Amaratunga, D; Shah, K; Watson, R; Singh, A; Allen, D; Shirani, J
Abstract: Background: Bedside assessment of intravascular volume in patients with chronic congestive heart failure (CHF) is often difficult. Under- and over-diuresis are common causes of morbidity and readmissions in these patients. Purpose: We hypothesized that ultrasound assessment of the internal jugular vein would be easier and more reproducible than clinically assessing jugular venous pressure (JVP). Our goal was to create a bedside test that would be simpler to learn than inferior vena cava (IVC) assessment and easier to perform in obese patients. Methods: Adults with HF (n=53, 52% men, mean age 65 years, mean BMI 29.6 kg/m 2, mean LVEF 44%) scheduled for right heart catheterization (RHC) had an ultrasound of their right internal jugular (RIJ) vein performed immediately prior. Cross-sectional area of RIJ was measured during normal breathing with patients at 90 and 45 degrees recumbency and was indexed by height (RIJI). JVP was also assessed clinically. Results were compared to right atrial pressure (RAP) measured by RHC. Operators were blinded to RHC results and vice versa. Results: JVP was correctly assessed clinically in only 43%. RIJI at 90 and 45 degrees were significantly larger in patients with elevated RAP compared to euvolemic patients (Table). At 90 degrees, RIJI of >15 predicted a RAP of >10 mmHg with 68% sensitivity and 72% specificity. At 45 degrees, RIJI of >10 predicted a RAP of >10 mmHg with 94% sensitivity and a negative predictive value of 80% (Table). Simply being able to see the RIJ at 90 degrees (n=34) had an 82.4% positive predictive value for elevated RAP. IVC data could not be obtained on 23% of patients due to body habitus or inability to lay flat. Conclusion: Ultrasonographic RIJI is more accurate than clinical assessment in patients with CHF and can be accurately performed even in obese patients. It requires only a basic linear ultrasound probe and was easily performed by clinicians at various stages of training with reproducible results. With the increased availability of bedside ultrasound in clinical practice, it is a feasible method of evaluating chronic CHF patients. FUNDunding Acknowledgement: Type of funding sources: None.